Behavioural Theories and Purchase Intention of Renewable Energy Technologies—A Meta-Analysis. (December 2022) - Gangakhedkar, Rajesh; Karthik, M.
Theory of planned behaviour (TPB) and technology acceptance model (TAM) are two behavioural theories that have been widely applied to understand the association between their constructs and purchase intention (PI) of renewable energy technologies (RETs). There is a need to synthesise these studies to understand the overall strength of association between their constructs and PI of RETs. With this objective in view, we conducted a meta-analysis of 41 studies that applied TPB and TAM or both to understand the PI of RETs. The results showed that all the constructs of TPB and TAM have a medium to large association, with perceived utility and attitude showing the strongest relationship with r = 0.536 and 0.487, respectively. To explore the reasons for heterogeneity in studies, moderator analysis was done by considering Hofstede's cultural dimension of individualism, the economic development level of the countries, and sample-related moderators such as the educational qualifications of the respondents. Moderator analysis gave mixed results.